FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATWAKTUAN PENYAJIAN LAPORAN KEUANGAN - Dwiyani, Sagung Agung; Badera, I Dewa Nyoman; Sudana, I Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.04.TAHUN 2017, 2017)
The purposes of this study are to obtain emperical evidence about the influence the structure of good corporate governance financial performance on the timeliness reporting in manufacturing industry and analyze the difference of market reaction between companies that provide financial statements on time and companies that provide financial statements not on time.The type of data that used is secondary data from annual reports during 2012-2015. Sampling technique used purposive sampling. Total population are 147 companies, based on the predetermined criteria, total samples are 58 companies. The data processed by using logistic regresion and independent sample t-test. The analysis showed that the audit committee, managerial ownership, and profitability have positif significant on the timeliness reporting while the independent commissioner, institutional ownership and leverage have insignificant. Further result of the study showed that no difference in market reaction on the companies that provide financial statement on time and companies that provide financial statement not on time.
Keywords: structure of good corporate governance, financial performance, timeliness reporting, and market reaction